Integration of the Eventlndex with other ATLAS systems. Issue 4 (December 2015) - Barberis, D.; Zárate, S.E. Cárdenas; Gallas, E.J.; Prokoshin, F.
Abstract: The ATLAS EventIndex System, developed for use in LHC Run 2, is designed to index every processed event in ATLAS, replacing the TAG System used in Run 1. Its storage infrastructure, based on Hadoop open-source software framework, necessitates revamping how information in this system relates to other ATLAS systems. It will store more indexes since the fundamental mechanisms for retrieving these indexes will be better integrated into all stages of data processing, allowing more events from later stages of processing to be indexed than was possible with the previous system. Connections with other systems (conditions database, monitoring) are fundamentally critical to assess dataset completeness, identify data duplication, and check data integrity, and also enhance access to information in EventIndex by user and system interfaces. This paper gives an overview of the ATLAS systems involved, the relevant metadata, and describe the technologies we are deploying to complete these connections.